The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1741-2552/ab1685
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ultrasound neuromodulation using a computationally efficient and interpretable model of intramembrane cavitation

Abstract: Objective. Low-intensity focused ultrasound stimulation (LIFUS) emerges as an attracting technology for noninvasive modulation of neural circuits, yet the underlying action mechanisms remain unclear. The neuronal intramembrane cavitation excitation (NICE) model suggests that LIFUS excites neurons through a complex interplay between microsecond-scale mechanical oscillations of so-called sonophores in the plasma membrane and the development of a millisecond-scale electrical response. This model predicts cell-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 34 publications
4
90
0
Order By: Relevance
“…Sundt unmyelinated membrane and SENN Ranvier nodes). We chose a typical sonophore radius (a = 32 nm) used in previous studies (Lemaire et al, 2019;Plaksin et al, 2016Plaksin et al, , 2014) and a physiologically plausible sonophore coverage fraction (fs = 80%) falling within a range of conserved excitability in cortical point-neuron models (see (Lemaire et al, 2019), Fig. 10).…”
Section: Lifus Modulates Membrane Capacitance To Excite Myelinated Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Sundt unmyelinated membrane and SENN Ranvier nodes). We chose a typical sonophore radius (a = 32 nm) used in previous studies (Lemaire et al, 2019;Plaksin et al, 2016Plaksin et al, , 2014) and a physiologically plausible sonophore coverage fraction (fs = 80%) falling within a range of conserved excitability in cortical point-neuron models (see (Lemaire et al, 2019), Fig. 10).…”
Section: Lifus Modulates Membrane Capacitance To Excite Myelinated Anmentioning
confidence: 99%
“…The SONIC paradigm relies on the assumption that membrane charge density and ion channel kinetics evolve at a much slower speed than microsecond-scale capacitance oscillations, thereby allowing for the accurate integration of neural responses using pre-computed cycle-averaged quantities of fast-oscillating variables. While that assumption is valid for point-neuron models (Lemaire et al, 2019), a recent study using a nanoscale two-compartment model have shown that under tight axial coupling conditions, strong intracellular currents mediate a significant intra-cycle charge redistribution that influences local membrane dynamics in a way that is not captured by the SONIC paradigm, resulting in overestimated sub-threshold charge build-ups and underestimated excitation thresholds (Tarnaud et al, 2020). It was also demonstrated that this numerical inaccuracy could be resolved by taking into account a limited number of Fourier components from precomputed oscillatory variables (as opposed to the SONIC approach that only considers their first component).…”
Section: Applicability Of the Sonic Paradigm In Multi-compartmental Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, triggerable drug-charged nanocarriers coupled withmultiple internal or external stimuli, such as pH, temperature,ultrasound, laser, and microwave radiation, have been extensivelyexplored for personalized treatment to enable controlled release.They have shown an excellent possibility to deliver enhancedanticancer treatment impact, with decreased systemic toxicity [12][13][14]. Low-intensity concentrated ultrasound (LIFUS) has beenexhaustively researched for tumor treatment along with the use ofultrasound imaging analysis as a potential exterior activate, whichis noninvasive and displays signi cant tissue-penetratingcapacity.…”
Section: Introductionmentioning
confidence: 99%
“…These systems have excellent potential for delivering enhanced anticancer treatment, while also decreasing systemic toxicity [12][13][14]. Low-intensity concentrated ultrasound (LIFUS) has been exhaustively researched for tumor treatment with ultrasound imaging analysis as one of the probable exterior activators, as it is non-invasive and displays significant tissuepenetrating capacity.…”
Section: Introductionmentioning
confidence: 99%